Efficacy and Safety of Dapagliflozin in Heart Failure With Reduced Ejection Fraction According to N-Terminal Pro-B-Type Natriuretic Peptide: Insights From the DAPA-HF Trial. (22nd November 2021) - Butt, Jawad H.; Adamson, Carly; Docherty, Kieran F.; de Boer, Rudolf A.; Petrie, Mark C.; Inzucchi, Silvio E.; Kosiborod, Mikhail N.; Maria Langkilde, Anna; Lindholm, Daniel; Martinez, Felipe A.; Bengtsson, Olof; Schou, Morten; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Effective therapies for HFrEF usually reduce NT-proBNP (N-terminal pro-B-type natriuretic peptide) levels, and it is important to establish whether new treatments are effective across the range of NT-proBNP. Methods: We evaluated both these questions in the DAPA-HF (Dapagliflozin and Prevention of Adverse Outcomes in Heart Failure) trial. Patients in New York Heart Association functional class II to IV with a left ventricular ejection fraction ≤40% and a NT-proBNP level ≥600 pg/mL (≥600 ng/L; ≥400 pg/mL if hospitalized for HF within the previous 12 months or ≥900 pg/mL if atrial fibrillation/flutter) were eligible. The primary outcome was the composite of an episode of worsening HF or cardiovascular death. Results: Of the 4744 randomized patients, 4742 had an available baseline NT-proBNP measurement (median, 1437 pg/mL [interquartile range, 857–2650 pg/mL]). Compared with placebo, treatment with dapagliflozin significantly reduced NT-proBNP from baseline to 8 months (absolute least-squares mean reduction, −303 pg/mL [95% CI, −457 to −150 pg/mL]; geometric mean ratio, 0.92 [95% CI, 0.88–0.96]). Dapagliflozin reduced the risk of worsening HF or cardiovascular death, irrespective of baseline NT-proBNP quartile; the hazard ratio for dapagliflozin versus placebo, from lowest to highest quartile was 0.43 (95% CI, 0.27–0.67), 0.77 (0.56–1.04), 0.78 (0.60–1.01), and 0.78 (0.64–0.95); P for interaction=0.09. Consistent benefits were observed for all-cause mortality. Compared with placebo, dapagliflozin increased the proportion of patients with a meaningful improvement (≥5 points) in Kansas City Cardiomyopathy Questionnaire total symptom score ( P for interaction=0.99) and decreased the proportion with a deterioration ≥5 points ( P for interaction=0.87) across baseline NT-proBNP quartiles. Conclusions: In patients with HFrEF, dapagliflozin reduced NT-proBNP by 300 pg/mL after 8 months of treatment compared with placebo. In addition, dapagliflozin reduced the risk of worsening HF and death, and improved symptoms, across the spectrum of baseline NT-proBNP levels included in DAPA-HF. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03036124.